Kebijakan Pengembangan Pariwisata Daerah (Kajian Di Kawasan Pangandaran Kabupaten Ciamis) - Sedarmayanti, Sedarmayanti (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
West Java has a great potency of tourism, the attraction and objects of tourist spread on each area. One of West Java main tourist objects is Pangandaran in Ciamis Regency. With its various superiorities, therefore the potency is strongly possible to be continously developed, so that it is expected to be able to increase the welfare of society. Up to now tourism becomes the second primadona in giving relatively great contribution to Product Domestic Regional Bruto after agriculture sector for Ciamis Regency.